Economía Social de Mercado versus capitalismo rentista. Reflexiones para América Latina* (2019)
The present article studies and compares three models of economic organization: the deregulatedeconomy, state capitalism, and the social market economy. Both the first and the second model are analyzed as paths that paradoxically lead in a similar direction: toward rentier or crony capitalism. On the other hand, the SME approach is presented as an alternative model, consisting of an institutional framework that proposes to prevent or combat rentier type behaviors. We argue that the Latin American region is experiencing a historical conjuncture which, despite structural challenges and an international context with a high dose of uncertainty and risks, seems conducive to discussing new concepts capable of harmonizing economic growth and social development.